Radiology MCQs for the new FRCR part 2A - Hussain, Shahid M.; Latif, Sherif; Colley, Steve; Tattersall, Debbie (Tfm Pub., 2006)
The Fellowship of the Royal College of Radiologists' Part 2A Examination has undergone significant changes and a format was initiated in Spring 2004. This book contains 500 multiple choice questions with short answers which are fully referenced allowing for additional reading. It is a useful tool for radiology registrars preparing for this exam.